Among Theory, Practice and Technology: the Relation Between Theoretical and Practical Knowledge in the Context of Accounting Training and the Thinking of Jürgen Habermas - Josicleide de Amorim Pereira Moreira (FUCAPE Business School, 2015)
The objective of this article is to analyze the relationship between theoretical and practical knowledge in accounting training based on the political-pedagogical foundations of higher education in the state of Paraiba. For that, we turn to the contributions of Jürgen Habermas’s theory of communicative action in order to understand how the relationship is established between theoretical discourse and practical discourse, drawing on definitions of "instrumental reason" and "communicative reason". To develop this empirical classification study, with a quantitative and qualitative approach, we employed the exploratory typology through bibliographic and documentary research. For data collection we applied a questionnaire with closed questions to students/interns of the public institutions analyzed. The results of the questionnaire show that the courses have an eminently theoretical format. Full-time practices are not applied and their focus is on the "modus operandi". We note that in accounting training, practice cannot be dissociated from theory and vice versa.